2001
DOI: 10.1128/mcb.21.14.4495-4504.2001
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe Cells Lacking the Amino-Terminal Catalytic Domains of DNA Polymerase Epsilon Are Viable but Require the DNA Damage Checkpoint Control

Abstract: In Schizosaccharomyces pombe, the catalytic subunit of DNA polymerase epsilon (Pol ) is encoded by cdc20 ؉ and is essential for chromosomal DNA replication. Here we demonstrate that the N-terminal half of Pol that includes the highly conserved polymerase and exonuclease domains is dispensable for cell viability, similar to observations made with regard to Saccharomyces cerevisiae. However, unlike budding yeast, we find that fission yeast cells lacking the N terminus of Pol (cdc20 ⌬N-term ) are hypersensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
106
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 49 publications
8
106
0
Order By: Relevance
“…Pol ⑀ has also been implicated in both DNA repair (Jessberger et al, 1993;Wang et al, 1993;Shivji et al, 1995;Holmes, 1999) and cell cycle checkpoint control in eukaryotic cells (Navas et al, 1995). Recently, we have shown that the DNA polymerase and exonuclease domains of Pol ⑀ are dispensable for cell viability in fission yeast (Feng and D'Urso, 2001). Similar observations have been made for the evolutionarily distant yeast, Saccharomyces cerevisiae (Kesti et al, 1999;Dua et al, 2000).…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Pol ⑀ has also been implicated in both DNA repair (Jessberger et al, 1993;Wang et al, 1993;Shivji et al, 1995;Holmes, 1999) and cell cycle checkpoint control in eukaryotic cells (Navas et al, 1995). Recently, we have shown that the DNA polymerase and exonuclease domains of Pol ⑀ are dispensable for cell viability in fission yeast (Feng and D'Urso, 2001). Similar observations have been made for the evolutionarily distant yeast, Saccharomyces cerevisiae (Kesti et al, 1999;Dua et al, 2000).…”
Section: Introductionsupporting
confidence: 67%
“…It should be noted that ChIP analysis is not sensitive enough to detect enrichment of Dpb2 or Mcm6 binding to origin DNA in exponentially growing populations where very few cells are in S phase. Therefore, considering that the amount of Dpb2 association to chromatin detected in cdc10-arrested cells is similar to the amount detected in either G2-arrested (cdc25) or exponentially growing 972 cells, we conclude that very little, if any, Dpb2 protein is bound to chromatin in the absence of Cdc10.In a previous study, we demonstrated that fission yeast cells are viable in the absence of the N-terminal, but not C-terminal half of the enzyme (Feng and D'Urso, 2001). This result was surprising because the N terminus of Pol ⑀ contains all the domains necessary for polymerase activity.…”
mentioning
confidence: 98%
See 3 more Smart Citations